A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) - Human, Brett A. (Zootaxa, 2006)
This paper examines the alpha level taxonomy of the genus Poroderma Smith, 1837 (Chondrichthyes: Scyliorhinidae), which is endemic to South Africa. A novel species identification key is presented for Poroderma, and a comprehensive review of the taxonomy (including type material and synonyms) and distribution of all taxa is presented. Conoporoderma Fowler, 1934 is shown to be a junior synonym of Poroderma Smith, 1837, P. marleyi Fowler, 1934 is shown to be a junior synonym of P. pantherinum, and a new colour form of P. pantherinum is described. This review is the first to offer a comprehensive description of the colour variation exhibited by P. pantherinum. The genus Poroderma contains the contemporary taxa P. africanum (Gmelin, 1789) and P. pantherinum (Smith in Müller and Henle, 1838).